Don't you feel well, Sam? - Hest, Amy. (Cambridge, Mass. : Candlewick Press, 2002)
When Sam has a cough, Mrs. Bear tends to him all through the cold night.
Accelerated Reader AR
Keywords: Mothers and sons -- Juvenile fiction; Bears -- Juvenile fiction; Sick -- Fiction; Mothers and sons -- Fiction; Bears -- Fiction